2013
DOI: 10.1097/mej.0b013e3283643801
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and symptoms of severe hypokalemia in emergency department patients

Abstract: Hypokalemia is common in the emergency department. Severe hypokalemia is often symptomatic and more than two-thirds of patients show ECG changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 0 publications
5
61
2
9
Order By: Relevance
“…Marti et al [12] reported that of 43,805 ED patients with serum potassium measurement, 4,826 (11%) had a potassium less than 3.5 mEq/L at presentation. Fifty-three patients had severe hypokalemia (<2.6 mEq/L), of which 26 (49%) were symptomatic and 20 (69%) had electrocardiogram changes.…”
Section: Introductionmentioning
confidence: 99%
“…Marti et al [12] reported that of 43,805 ED patients with serum potassium measurement, 4,826 (11%) had a potassium less than 3.5 mEq/L at presentation. Fifty-three patients had severe hypokalemia (<2.6 mEq/L), of which 26 (49%) were symptomatic and 20 (69%) had electrocardiogram changes.…”
Section: Introductionmentioning
confidence: 99%
“…Disorders of serum sodium and potassium are common in outpatients and were found to be present in more than 10% of patients, respectively [1,2,3]. Many factors have been found to be associated with the development of dysnatremias and dyskalemias, with diuretic therapy being the most prominent [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Entre las más comunes están el ayuno, el uso de diuréticos o de beta 2 adrenérgicos, las infusiones de dextrosa y/o insulina y las pérdidas gastrointestinales (4)(5)(6)(7)(8). Por lo general, su corrección es sencilla, pero en algunas ocasiones es recurrente y de tratamiento difícil.…”
Section: Discussionunclassified
“…Por lo general, su corrección es sencilla, pero en algunas ocasiones es recurrente y de tratamiento difícil. Un nivel de potasio muy bajo (menor de 2,6 mEql/L) puede poner en riesgo la vida del paciente por parálisis, rabdomiolisis, insuficiencia respiratoria, arritmias o paro cardíaco; además, dificulta el tratamiento de otras enfermedades por íleo paralítico, que impide la nutrición y la tolerancia a los medicamentos (7,(9)(10)(11). Por lo anterior, es fundamental buscar sistemáticamente las causas corregibles, con el fin de instaurar un tratamiento apropiado, dirigido, y evitar así complicaciones graves (8 Figura 2.…”
Section: Discussionunclassified